Representation of stories associated with Malay myths and legends in contemporary mass media / Norhanim Abdul Razak ... [et al.] - Abdul Razak, Norhanim; Omar, Hamimi; Ibrahim, Johan Afendi (2015)
It appears that stories associated with ancient myths and legends have been featured more often in the mass media around the world including Malaysia. While the significance of mythological tales in the lifestyle of the Malays has been noted by previous scholars, there are, however, limited studies which have examined this topic from the perspective of mass media. Hence, the aim of this paper is to explore the representation of stories related to the Malay myths and legends in the Malaysian mass media. The analysis focuses on two well-known Malay mythological tales published in the newspapers for the past 15 years (2000 to 2015) using a content analysis technique. It is found that stories linking to Mahsuri and Raja Bersiong (the Fanged King) have been featured in several local newspapers such as Berita Harian, News Straits Times and The Star. In the case of Mahsuri legend, stories narrating her seven generation curse or ‘sumpahan’ and events in celebrating her seventh generation’s wedding were widely reported. Parts of Mahsuri legend often depicted in the articles include stories of her having white blood and the curse uttered by her before she was killed. For Raja Bersiong, narratives of his legend mainly consist of tales of a cruel king who had fangs and a strong thirst for human blood. The link of this raja to the name of a town named ‘Baling’ and a mysterious castle in Jitra are stated as well. Overall, findings of this paper contribute to the understanding of the representation of Malay tales in contemporary mass media by revealing that, in addition to the narratives, recent developments linked to past mythical figures, events and statements to verify the authenticity of myths and legends, and values have been presented in the newspapers.